MSC virtual e-abstract (CPP-02) - Stroke Conference 2020, Malaysia (Journal Of Cardiovascular, Neurovascular & Stroke, 2020)
Corticospinal tract (cst) structural integrity as the imaging marker of functional motor recovery outcome in stroke rehabilitation. A systematic review and meta-analysis: The effects of vegetarian diets on systolic and diastolic blood pressure. Association of stroke severity and risk factors with the local ethnic community of seberang prai - 4 months review from acute stroke unit, Seberang Jaya Hospital. Angioedema secondary to iv alteplase for acute ischemic stroke. Young stroke with antiphospholipid syndrome and nephrotic syndrome. Multidisciplinary management of a hemorrhagic stroke during pregnancy with a successful functional outcome. The light at the end of tunnel for management of acute ischemic stroke with large vessel occlusion in non-neurologist hospital.